Activity of the aqueous extract of Schinus terebinthifolius Raddi on strains of the Candida genus - Kátia Andrea de Menezes Torres; Sônia Maria Rolim Rosa Lima; Suely Mitoi Ykko Ueda (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
ABSTRACT Objectives: To evaluate the antifungal susceptibility profile of the aqueous extract of the bark of Schinus terebinthifolius Raddi against the strains of the genus Candida. Methods: By using the disk diffusion method, 50 samples of the genus Candida (Candida albicans; Candida krusei; Candida glabrata; and Candida tropicalis), isolated from patients receiving treatment at Hospital Santa Casa de Misericórdia de São Paulo, and 1 American Type Culture Collection (ATCC) sample of each species were tested against: the isolated aqueous extract of the bark of Schinus terebinthifolius Raddi, isolated nystatin, and the association of nystatin and the aqueous extract of Schinus terebinthifolius Raddi. Results: There were no significant differences regarding the different strains of Candida tested. In the presence of the aqueous extract of Schinus terebinthifolius Raddi, no inhibition halo was visible. Isolated nystatin formed an inhibition halo measuring respectively 18.50 mm and 19.50 mm for the Candida albicans species and the others referred to as non-Candida albicans (Candida krusei; Candida glabrata; and Candida tropicalis). The association of nystatin and the aqueous extract of Schinus terebinthifolius Raddi resulted in inhibition halos measuring 14.25 mm and 16.50 mm respectively. The comparisons of these results are statistically significant (p < 0,001). Conclusion: The aqueous extract of Schinus terebinthifolius Raddi showed no antifun-gal activity in vitro against the strains tested, whereas the association of nystatin and the aqueous extract of Schinus terebinthifolius Raddi caused a decrease in the inhibition halo when compared with isolated nystatin.